Selective photochemical synthesis of Ag nanoparticles on position-controlled ZnO nanorods for the enhancement of yellow-green light emission. Issue 48 (25th November 2015) - Park, Hyeong-Ho; Zhang, Xin; Lee, Keun Woo; Sohn, Ahrum; Kim, Dong-Wook; Kim, Joondong; Song, Jin-Won; Choi, Young Su; Lee, Hee Kwan; Jung, Sang Hyun; Lee, In-Geun; Cho, Young-Dae; et al.
Abstract : The photoluminescence of ZnO nanorod arrays is tailored by formation of Ag–ZnO hybrids. Abstract : A novel technique for the selective photochemical synthesis of silver (Ag) nanoparticles (NPs) on ZnO nanorod arrays is established by combining ultraviolet-assisted nanoimprint lithography (UV-NIL) for the definition of growth sites, hydrothermal reaction for the position-controlled growth of ZnO nanorods, and photochemical reduction for the decoration of Ag NPs on the ZnO nanorods. During photochemical reduction, the size distribution and loading of Ag NPs on ZnO nanorods can be tuned by varying the UV-irradiation time. The photochemical reduction is hypothesized to facilitate the adsorbed citrate ions on the surface of ZnO, allowing Ag ions to preferentially form Ag NPs on ZnO nanorods. The ratio of visible emission to ultraviolet (UV) emission for the Ag NP-decorated ZnO nanorod arrays, synthesized for 30 min, is 20.5 times that for the ZnO nanorod arrays without Ag NPs. The enhancement of the visible emission is believed to associate with the surface plasmon (SP) effect of Ag NPs. The Ag NP-decorated ZnO nanorod arrays show significant SP-induced enhancement of yellow-green light emission, which could be useful in optoelectronic applications. The technique developed here requires low processing temperatures (120 °C and lower) and no high-vacuum deposition tools, suitable for applications such as flexible electronics.